DEMOCRATIC CRISIS IN INDONESIA’S ADMINISTRATIVE LAW RELATED TO RUU DKJ PROPOSED BY DPR RI - Alexandra Denise Setia Santosa; Meida Wulansari2 Meida Wulansari2; Michelle Angela Kawanda; Vanessa Manuela Patty; Vina Julfiana Wibowo (Problematika Hukum, 2021)
The crisis is a critical situation and democracy is an idea or outlook on life that prioritizes equal rights and obligations as well as equal treatment for all citizens. The democratic crisis in Indonesia is getting worse thanks to the passing of the Draft Law on the Special Region of Jakarta (RUU DKJ) on Tuesday, December 5 2023 by the House of Representatives. In the Draft Law on the Special Region of Jakarta (RUU DKJ) it is written that the Governor and Deputy Governor are appointed by the President and the Mayor and the Regent are appointed by the Governor. Draft laws should be made in the interests of the people with democratic values. However, it is very unfortunate that several decisions in the Draft Law on the Special Region of Jakarta (RUU DKJ) are not in line with this principle. This research will examine the problem by referring to the 1945 Constitution and Law Number 6 of 2020, using qualitative and evaluation methods to explore the impact and implications of the DKJ Bill on democracy in Indonesia.Keywords: Crisis; Democracy; Rancangan Undang-Undang; House of Representative; Government.